Gallstones and cholecystectomy in modern Britain - Bateson, M (BMJ Group, 2000)
BACKGROUND—It has been suggested that gallstone disease is now commoner, and that this might explain an increase in cholecystectomy rates, though conclusive evidence has been lacking. METHODS—All the non-forensic necropsy results for Dundee 1953-98 were examined to assess the prevalence of gallstone disease. The NHS Scotland annual cholecystectomy figures were extracted from their earliest availability in 1961 up to the present. The subgroup of patients from Dundee was analysed separately, as were laparoscopic procedures, which were recorded from 1991. RESULTS—Gallstone disease was much commoner in 1974-98 than in 1953-73. Increasing age was the main determinant of gallstone disease. Though gallstone disease was commoner in women than men aged 40-89, there was no sex difference under 40 or over 90 years. Cholecystectomy became much commoner in the 1960s when frequency of gallstone disease did not change. It increased further in the 1970s, peaking in 1977-8. There was a gradual fall in rates in the 1980s when gallstone prevalence remained high. There was a further moderate rise in the 1990s after the wide introduction of laparoscopic cholecystectomy. Cholecystectomy is now much commoner in young women and this change started in the 1960s. By contrast, cholecystectomy in men has become more prevalent in the older age group. CONCLUSIONS—Gallstones were definitely more common in both sexes at all ages over 40 in the last 25 years. Changes in the cholecystectomy rates are only partly explained by changes in gallstone prevalence, and are more determined by surgical practice.   Keywords: cholecystectomy; gallstones